2008
DOI: 10.3923/pjbs.2008.2532.2544
|View full text |Cite
|
Sign up to set email alerts
|

Habitats and Plant Communities in the Nile Delta of Egypt I. Deltaic Mediterranean Coastal Habitat

Abstract: The present study aims at investigating the vegetation-soil relationships in the Deltaic Mediterranean coastal land of Egypt. The Deltaic coast of the Mediterranean Sea of Egypt can be distinguished into five habitat types, namely: sand dunes, salt marshes, sand sheets, sandy fertile lands and lake shorelines (Manzala, Burullus and Idku). These habitats are categorized into four vegetation groups namely, group A dominated by Rumex pictus, group B codominated by Pancratium maritimum-Cyperus capitatus-Lolium per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
5
10
0
Order By: Relevance
“…The lifeform spectra are important physiognomic attributes which have widely used by ecologists and chorologists in the vegetation and floristic studies (Cain and Castro 1959). In the present study, the life-form spectrum is predominantly therophytes (43 % as reported by Mashaly et al, 2008).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The lifeform spectra are important physiognomic attributes which have widely used by ecologists and chorologists in the vegetation and floristic studies (Cain and Castro 1959). In the present study, the life-form spectrum is predominantly therophytes (43 % as reported by Mashaly et al, 2008).…”
Section: Discussionmentioning
confidence: 52%
“…The vegetation of the present study was classified by TWINSPAN into thirteen groups. G1 was dominated by Lotus halophilus and represent island sand dunes Mashaly (2008). G2 and G 5 dominated by Alhagi graecorum, Stipagrostis lanata respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 e Poor soils; those include bare soils which have a finer texture (sample 14). 5 e Very poor soils; those comprise all the other bare soils (samples 7,8,9,10,11,12,13,15,16,17,18,19,20). The most obvious results of these classification systems indicate that bare lands of Damietta Governorates are not suitable for agricultural purposes.…”
Section: 5mentioning
confidence: 95%
“…The only vegetation cover is represented by halophytic vegetation. Plant species occurring at the region are Arthrocnemum macrostachyum and Atriplex portulacoides [20].…”
Section: Soil Formationmentioning
confidence: 99%